The Translation Of Idioms In The Netflix Subtitle Of The Film Notting Hill - I Kadek Arditya Kurniawan; I Nengah Sudipa; Ketut Santi Indriani (Indonesian Journal of Science, Technology and Humanities, 2024)
Idiom is one of the most complicated figurative languages for translators to render, since not all of them have the exact equivalent in another language. Related to the issue, the current study was conducted. It was a qualitative study. The data were taken from the transcript of the film “Notting Hill”, and its Indonesian translated subtitle by Netflix’s team. In analyzing the types of idioms and the translation strategies used in the subtitle, theories proposed by Fernando (1996) and Baker (2011) were used. From the analysis, it can be concluded that Pure Idiom was the most frequently found type of idiom in the movie with 35 idioms or 51% of the data, and Translation by Paraphrase was the most frequently used idiom translation strategy with 51 idioms or 75% of the data